[en] EVALUATION OF THE REQUIREMENTS AND COMMERTIALIZATION OF THE POWER RESERVE IN COMPETITIVE SYSTEMS - ANDRE LUIS MARQUES MARCATO (MAXWELL, 2005)
[pt] Este trabalho apresenta diversas metodologias para o cálculo de pagamento pela reserva de capacidade do sistema. A remuneração da reserva oferecida pelo sistema vem sendo cada vez mais discutida, principalmente, devido ao aumento de competição no setor elétrico e sua possível influência negativa na confiabilidade de suprimento. O estudo da confiabilidade do sistema tem uma ligação direta com este problema, pois os seus índices podem medir a importância da reserva de potência para o desempenho do sistema. Da mesma forma, a precificação de reserva procura refletir os requisitos de confiabilidade do sistema. Com isto é esperado que os agentes procurem agregar reserva ao sistema quando devidamente compensados por isto. As diversas maneiras de obterem-se os índices de confiabilidade são apresentadas, bem como as vantagens e desvantagens de cada uma. Os métodos discutidos são importantes para o sistema brasileiro, pois levam em consideração a confiabilidade composta geração- transmissão. Em um país com grande extensão territorial e com uma malha de transmissão na avaliação do risco do sistema. Foram utilizados como casos exemplos para este trabalho um sistema teste de 3 barras criado especialmente para este estudo, o IEEE-MRTS (IEEE-Modified Realiability System), e um equivalente do Sistema Sul-Sudeste Brasileiro. Finalmente, são discutidas as diversas maneiras que os agentes podem pagar e receber pela reserva operativa. O objetivo é tentar reduzir ao máximo a grande variância existente neste pagamento, pois se este valor for calculado em tempo real, é fácil perceber que os geradores receberão muito pouco em épocas de pequena demanda de energia, e por outro lado, receberão altas quantias nos instantes de pico de carga ou períodos secos. === [en] This work presents various methodologies for the calculation of payment through system capacity reserve. The remuneration of energy reserve offered by the system is been more and more discussed, mainly owing to increase of competition in electrical sector and its possible negative influence in supply reliability. The study of system reliability has a direct connection to this problem, because their indices can measure the importance of energy reserve for the performance of the system. Furthermore, the reserve tariff tries to reflect system reliability requirements. So, the system wait for investments of agents, when their receive correct remuneration for this. The various ways of getting the reliability indices are shown, as well as the advantages and disadvantages of each one. The methods discussed are important for the Brazilian System because they take into consideration the generation-transmission reliability, while the methods used in the majority of other countries only taking consideration the generation. In large countries and with a transmission network completely interconnected as in Brazil, it is indispensable the study of the impact of transmission network in the evaluation of system risk. The cases studies for this work have used the IEEE-MRTS (IEEE-Modified Reliability System), a test system of three buses specially designed for this study and a equivalent of South-Southeast Brazilian Case (SSB). Finally, different way that agents can pay or receive in a accord with capacity of operative reserve are discussed. The objective is to try to reduce the maximum the great variation existing in this payments, because if this value was calculated in real time is easy to see that the generation will receive much less in time of low energy demand, and on the other hand, will receive high amounts in times of the load peak or dry periods.